The effect of internal control environment on operational risk of quoted banks in Nigeria - Chidinma N., Ozuomba; Eugene O., Nwadialor,; Alphonsus S., Anichebe, (International Journal of Scientific Research and Management (IJSRM), 2019)
Banks are more likely to fail from operational risk than from credit risk, and internal control at banks create operational risk losses. Internal control system is the backbone of every company and the successful attainment of the goals of most companies depend upon the effectiveness of their policies and internal control system. The objective of this study is to investigate the effect of internal control environment on operational risk of quoted banks in Nigeria. 16 selected quoted banks in the Nigerian stock exchange from 2013-2017 were studied based on the 2012 banking reform on corporate governance by the then CBN governor Sanusi Lamido Sanusi’s “Project Alpha Initiative” (PAI). Data were collected from banks published annual reports, CBN statistical bulletin, NDIC report, CBN fact book, company website and banks’ Pillar III disclosure report for the relevant years sampled for analysis. The analysis carried out included pooled OLS regression, fixed and random effect and Hausman tests to determine the most suitable model for result interpretation. This was conducted with the aid of E-View 7 software. The findings shows that internal control environment (BS, ID, LD, and ES) has positive significant effect on Operational risk (OPR). It was recommended that a well-established internal environmental control system should be mandatory for all companies, in the banking industry.